The use of portfolios for continuing assessment of physiotherapy students in clinical practice settings - N. Naidoo (AOSIS, 2004)
Many and varied methods of assessment are used to evaluate undergraduate physiotherapy students. Different modes of assessment occur as a result of contrasting educational theories and because the purpose of assessment is variable. In this era of performance assessment related to  the students' mastery of the core curriculum, portfolios can enhance the assessment process by revealing a range of skills and understandings. This fits snugly into the physiotherapy curriculum for undergraduate continuous assessment purposes. Portfolio assessment can facilitate more reflection on students' learning, more ownership of learning and more awareness of self-development. This supports the South African Qualifications Authority's objective for higher education of reflection and life-long learning in our students. This article presents discussion on the use of portfolios in physiotherapy student learning and assessment in clinical practice.